Factors Affecting Decision to Participate Bancassurance: Evidence from Individual Customers in the South of Vietnam - Dong, Khuu Thi Phuong; Hoa, Nguyen Thi Ngoc; Khoi, Phan Dinh; Giao, Ho Thi Huynh; Suong, Huynh Thi Tuyet; Quyen, Diep Tran Hoang (International Journal of Economics and Financial Issues, 2024)
This study aims to investigate factors effect on decision to participate the Bancassurance of individual customers in the South of Vietnam. Binary Logistic regression model was explored to investigate the factors affect on the decision to participate in life insurance through Bancassurance channel. The data was collected by interview survey of 62 individual customers who have participated and not participated the life insurance through Bancassurance. Found results indicated that the customer’s income and the professional of insurance companies’ advisors have positive significantly effects on the decision to participate in life insurance products via Bancassurance channel of personal customers in Can Tho city, Vietnam. Based on the results, the diversification of payment policies for customers with different groups of income level should be considered to enhance the enhance the decision to participate Bancassurance. The trust, creditability and transparency of information sharing by insurance companies’ advisors should be ensured to improve the confidences of customers on the advisor consultants.